Incidental paranasal sinus abnormalities on CT of children: clinical correlation. - Glasier, C M; Ascher, D P; Williams, K D (American Journal of Neuroradiology, 1986)
The paranasal sinuses were prospectively evaluated by CT, clinical history, and physical examination in infants and children having cranial CT for indications unrelated to upper respiratory inflammation (URI). One hundred and one CT scans were studied, and sinus abnormalities were detected in 18% of patients older than 1 year and without signs or symptoms of URI. When signs and/or symptoms of recent URI were present, the incidence of abnormalities was 31%. Maxillary antral were not identifiable or were opacified in 72% of all infants under 1 year old. Because of the high incidence of sinus abnormalities on CT in children with and without evidence of recent URI, abnormalities should not be ascribed to sinusitis without close clinical correlation.